Secure rubber plate - Ahmad Ridhuwan Abdullah; Mohd Zulkifli Muhammad; Razman Hafifi Redzuan (2012)
High rubber prices forcing residents in several villages in the district to build huts and camp for the night in their gardens to prevent theft of rubber. Rubber theft becoming prevalent not only at night but in the afternoon since the commodity price increases. From the survey more than 10 incidents of theft have been reported within 15 days. With invention of this product, the stolen number of rubber can be reduce because each of rubber estate/ farmer has their own serial plate (Regulated by Malaysian Rubber Board) which each buyer / wholesaler of rubber being enforce to record and accept rubber only with a serial.